Risk factors for non communicable diseases among transport and security personnel of a health sciences university in coastal Karnataka - Audichya, Sumit; H., Pavithra; V., Harikrishnan; Akshaya, Kibballi Madhukeshwar (International Journal Of Community Medicine And Public Health, 2020)
Background: Non communicable diseases (NCDs) are on the rise among workers in various occupations resulting in morbidity and mortality. This study was conducted to assess the various risk factors and associated socio-demographic factors among the security and transport personnel working in a health sciences university in Mangaluru. Methods: It was a cross-sectional study conducted among all the security and transport personnel. Questionnaire based on WHO-STEPS approach was used. Blood pressure (BP) measurements were recorded. Results: Total 167 study participants were enrolled; 57.5% were security and rest were transport personnel. Physical activity was perceived as light by 63.5% participants. Current smokers constituted to 26% and 33.5% consumed alcohol in past 12 months. Eighteen percent of them top salted their food. Among participants who were apparently healthy, 12.5% and 23.4% had raised systolic and diastolic BP. Associations between the areas of residence (p=0.004) and type of occupation (p<0.001) were found to be significant. Conclusions: Prevalence of risk factors of NCDs was high among study participants. Only few study subjects were physically active and majority of them felt that their routine work provided them with light physical activity. Around one third of the participants consumed tobacco and alcohol. Around 1/4th of the study participants who were not known hypertensive, were found with increased levels of blood pressure.